Pengaruh Brand Trust, Customer Value dan Customer Experience terhadap Customer Satisfaction pada CV. Syifa Adventure - Maulida, Wildan Uyunina; Andari, Titiek Tjahja; Yulianingsih, Yulianingsih (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
Based on the research results and hypothesis testing regarding the influence of brand trust, customer value, and customer experience on customer satisfaction at CV Syifa Adventure, the following conclusions were obtained: Consumer responses to brand trust, customer value, and customer experience on customer satisfaction show that brand trust (X1) has an average rating in the moderately suitable category, with brand honesty as the highest-rated indicator, indicating CV Syifa Adventure's priority on product safety, while the lowest-rated indicator is brand security, indicating that the CV Syifa Adventure brand is easily counterfeited. Customer value (X2) also shows an average rating in the moderately suitable category, with quality value as the highest-rated indicator, indicating consumer satisfaction with the quality of rafting equipment (life jackets, helmets, paddles) and the overall rafting experience, while the lowest-rated indicator is social value, indicating that rafting activities do not help expand social networks. Customer experience (X3) shows an average rating in the moderately interesting category, with action (act) as the highest-rated indicator, indicating smooth rafting activities and good team dynamics, while the lowest-rated indicator is the senses (sense), indicating a lack of cleanliness in the rafting area. Customer satisfaction (Y) is considered moderately satisfactory, with adequate supporting facilities as the main factor in consumers' decisions to recommend CV Syifa Adventure, while the lowest-rated indicator is expectation conformity, indicating that the service received does not meet or exceed expectations. Based on hypothesis testing (F-test), brand trust (X1), customer value (X2), and customer experience (X3) simultaneously have a positive and significant effect on customer satisfaction. Based on partial hypothesis testing (t-test), brand trust (X1), customer value (X2), and customer experience (X3) do not have a negative and significant effect on customer satisfaction (Y).